Unseen: Advancing Digital Accessibility with Binaural Audio Technology in an Immersive Gaming Prototype - Claudia Susie C. Rodrigues; Vitoria Nazareth; Ramon O. Azevedo; Priscyla Barbosa; Cláudia Werner (Journal on Interactive Systems)
The growing significance of accessibility, particularly in the realm of disability rights, is unmistakable. "Unseen" emerges as a prototype leveraging binaural audio technology to craft an immersive 3D gaming experience, placing a paramount focus on promoting accessibility and digital inclusion. Its primary objective is to deliver a immersive audiogaming encounter, catering to both sighted gamers and individuals with visual impairments. Through a comprehensive evaluation of the prototype, the efficacy of its audiogame interactions and mechanisms was assessed. Valuable insights gleaned from laboratory tests not only pinpointed areas for game enhancement but also shed light on elements that fostered user satisfaction and motivation. These research results notably exemplify promoting digital accessibility in gaming, particularly through the utilization of binaural audio, and the active engagement of individuals with visual impairments in the virtual environment.